EFFORTS TO STRENGTHEN THE HUMAN CAPACITY OF CAKE UMKM THROUGH MANAGERIAL EDUCATION AND PRACTICAL ACCOUNTING BASED ON AN INTERACTIVE MODULE IN SERANG DISTRICT BANTEN - Afriani, Raden Irna; Yuliah, Yuliah; Puspa, Rani; Permana, Angrian; Husni, Mohamad; Khodijah, Ina; Octavitri, Yollanda (Yayasan Education and Social Center, 2025)
This community service activity aims to strengthen the human resource capacity of cake MSMEs in Serang Regency, Banten through practical managerial and accounting education based on interactive modules. This training was held in February 2025 and involved MSME players who previously had limited knowledge in business management and accounting. The method used is interactive module-based training which includes material on business management, financial planning and simple accounting records. Evaluation results show significant improvements in managerial understanding, accounting skills, and application of acquired knowledge in their businesses. Before the training, participants had limited basic knowledge, but after the training, the majority of participants were able to manage business finances in a more structured and systematic manner. The increase in participant satisfaction with the training was also very high. This activity succeeded in increasing the capacity of MSME players to be more efficient in managing their businesses, which is expected to increase the competitiveness of MSMEs in the area.